An overview of municipal solid waste management and landfill leachate treatment: Malaysia and Asian perspectives - Kamaruddin M.A.; Yusoff M.S.; Rui L.M.; Isa A.M.; Zawawi M.H.; Alrozi R. (Springer Verlag, 2023)
biochemical oxygen demand; biogeochemistry; concentration (composition); developing world; landfill; leachate; municipal solid waste; operations technology; physicochemical property; waste management; wastewater; Malaysia; analysis; Malaysia; procedures; solid waste; waste disposal; waste disposal facility; water management; water pollutant; Malaysia; Refuse Disposal; Solid Waste; Waste Disposal Facilities; Water Pollutants, Chemical; Water Purification